Where azaleas bloom - Woods, Sherryl (Woods, Sherryl. Sweet magnolias., 2012)
Single mother Lynn Morrow discovers the healing power of love when contractor Mitch Franklin, a widower with two grieving sons, comes to her rescue and helps her to find her own way.